STUDI KASUS PERAN ORANG TUA DALAM PENANAMAN NILAI-NILAI AGAMA BAGI ANAK USIA DINI DI DUSUN CAOWAN RT 017 RW 005 DESA KRAMATAGUNG KECAMATAN BANTARAN KABUPATEN PROBOLINGGO - saniti; Dirgayunita , Aries (LPPM IAD Probolinggo, 2024)
The role of parents in instilling religious values For early childhood it is very important because the parents are madrosatul ula. And how parents are instilling religious values to their children. This research method is a qualitative case study method. It was carried out at Dusun Caowan Rt 017 Rw 005 Kramatagung Village, from September 04-30 November 2023. With 10 research subjects. The research findings include the application of religious values to early childhood with the practice of inviting children to pray five times, teaching children how to respect older people, practicing fasting, learning children to speak polite and also teaching their children to read the Qur'an. Methods or methods taken by parents in applying religious value to children by direct example, advising or giving understanding, instilling love of God and His Apostle, inviting kids to religious activities, cultivation or practice and not forgetting the methods of prayer or anointing to God for their children. Keywords: Role of Parents, Religious Values, Early Childhood